Investigating and explaining organizational antecedents of PSM. Issue 1 (2014) - ,; ,
Abstract : Purpose – First, the purpose of this paper is to contribute to the public service motivation (PSM) literature by increasing the limited knowledge of organizational antecedents of PSM. Second, by combining PSM with insights from self‐determination theory (SDT), the paper aims to elucidate the link through which high‐performance work systems (HPWS) relate to PSM.Design/methodology/approach – Using a survey, the authors investigated nurses' perceptions of HPWS, PSM, and the satisfaction of basic psychological needs in four different German hospitals.Findings – The results of this study provide empirical evidence that PSM is influenced by several HR practices and the three basic psychological needs autonomy, relatedness, and competence, which in turn are influenced by certain HR practices as well. Basic psychological needs do not fully mediate the relationship between HPWS and PSM.Research limitations/implications – Four dimensions of HPWS are measured by a single item and the results are based on a German sample. They therefore might not apply to other countries. Future research will benefit from using a more corroborated measurement instrument of HPWS in different countries.Practical implications – This study offers useful insights for HR managers in the nursing sector on the question how PSM can be fostered effectively.Originality/value – This study adds to the limited knowledge of organizational antecedents of PSM by including ideas from HRM into the study of PSM. Second, by combining PSM with insights from psychology (SDT), this study sheds light on the mediating mechanisms which help to explain how HPWS relate to PSM; a conceptual model explaining the HPWS‐PSM relationship is developed and tested. Acknowledgements : At the time the research was completed C. Schott was affiliated to the Utrecht School of Governance, Utrecht University, Utrecht, The Netherlands. The authors thank Wouter Vandenabeele for helpful comments on a previous version of this paper. This paper was co‐financed by NWO (the Netherlands Organization for Scientific Research).